2020
DOI: 10.37825/2239-9747.1011
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced Sleep Endoscopy (DISE) with Simulation Bite to Predict the Success of Oral Appliance Therapy in Treating Obstructive Sleep Apnea/Hypopnea Syndrome (OSAHS)

Abstract: Study objectives Oral appliances have gained their place in the treatment of obstructive sleep apnea (OSA) where custom-made titratable mandibular advancement devices (MAD) have become the oral appliance of choice. This study aimed to asses the value of the drug-induced sleep endoscopy (DISE) using a MAD in the prediction of treatment outcome for OSAHS Methods This is a prospective, single-center cohort study that enrolled sixty-six consecutive patients with diagnosed O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…That is, the integration of various conservative treatments, such as OA, positional therapy, intermittent negative airway pressure, weight control, and several kinds of surgical treatments, may effectively treat OSA, especially CCC. [19][20][21] In our study, 32 patients (39%) had positional OSA. Our study found that upper airway patency improved in a proportion of patients during head rotation or with OA use, and some patients did not improve.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…That is, the integration of various conservative treatments, such as OA, positional therapy, intermittent negative airway pressure, weight control, and several kinds of surgical treatments, may effectively treat OSA, especially CCC. [19][20][21] In our study, 32 patients (39%) had positional OSA. Our study found that upper airway patency improved in a proportion of patients during head rotation or with OA use, and some patients did not improve.…”
Section: Discussionmentioning
confidence: 47%
“…Therefore, we can use these DISE modification findings to adjust our future surgery and treatment protocol. That is, the integration of various conservative treatments, such as OA, positional therapy, intermittent negative airway pressure, weight control, and several kinds of surgical treatments, may effectively treat OSA, especially CCC 19‐21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since MADs maintain airway patency by displacing the mandible and attached soft tissues forward, the assumption is that the site of collapse during sleep is an important parameter to predict the responsiveness of the treatment [ 62 ]. In this regard, primary oropharyngeal collapse, both at the level of the soft palate and tongue base, was associated with positive treatment response and should be considered a predictor of MAD response [ 29 , 39 , 63 ].…”
Section: Resultsmentioning
confidence: 99%